2014
DOI: 10.3390/s140203207
|View full text |Cite
|
Sign up to set email alerts
|

Mapping and Evaluating the Urbanization Process in Northeast China Using DMSP/OLS Nighttime Light Data

Abstract: In this paper, an Urban Light Index (ULI) is constructed to facilitate analysis and quantitative evaluation of the process of urbanization and expansion rate by using DMSP/OLS Nighttime Light Data during the years from 1992 to 2010. A unit circle urbanization evaluation model is established to perform a comprehensive analysis of the urbanization process of 34 prefecture-level cities in Northeast China. Furthermore, the concept of urban light space is put forward. In this study, urban light space is divided int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(48 citation statements)
references
References 40 publications
1
45
0
Order By: Relevance
“…Yi and his colleagues proposed an Urban Light Index (ULI) to evaluate the urbanization process in 34 prefectural cities in Northeast China. They found that the ULI has increased during 1992-2010, and the urbanization is most significant during 2004-2010 [54]. Huang and his colleagues made use of night light images to evaluate city size and rank in China during 1992-2008, they found that the distribution of city sizes became more even during the period and the greatest change in city size distribution occurred during 2000-2003 [42].…”
Section: Introductionmentioning
confidence: 99%
“…Yi and his colleagues proposed an Urban Light Index (ULI) to evaluate the urbanization process in 34 prefectural cities in Northeast China. They found that the ULI has increased during 1992-2010, and the urbanization is most significant during 2004-2010 [54]. Huang and his colleagues made use of night light images to evaluate city size and rank in China during 1992-2008, they found that the distribution of city sizes became more even during the period and the greatest change in city size distribution occurred during 2000-2003 [42].…”
Section: Introductionmentioning
confidence: 99%
“…The inter-calibration of the datasets was conducted by using second order polynomial regression (Eq. 1) (Yi et al, 2014). The calibrated DNs were calculated as:…”
Section: Urban Expansion Estimation By Dmsp/olsmentioning
confidence: 99%
“…Such rapid urbanization has spurred natural resource depletion and a series of ecological and environmental problems [7,8], e.g., quality deterioration, pollution of urban surface water, exacerbated urban heat island effects, and the degradation of ecosystem functioning [9,10]. Therefore, a timely and general analysis of urban expansion (e.g., expansion rates, expansion patterns, and expansion evaluations) is crucial to understanding the characteristics of for 1992 to 2010 and quantitatively evaluated the urbanization processes and expansion rates of 34 prefecture-level cities in northeastern China [41]. Li derived a time series vegetation adjusted NTL urban index (VANUI) from DMSP/OLS data and analyzed urban dynamics of the southeastern United States for 1992 to 2013 [42].…”
Section: Introductionmentioning
confidence: 99%